Entrepreneuring as existential transformation: a review of entrepreneurial identity with a typology of career and personal change - Tolulope B. Oluwafemi; Angus J. Duff (Cogent Business & Management)
Emancipatory entrepreneuring, the actions taken to liberate oneself from work and life constraints, transforms the lives of entrepreneurs’ and has implications for entrepreneurial identity. However, this phenomenon is poorly understood. In this conceptual paper, we draw from literature of entrepreneurial discovery and emancipatory entrepreneuring to develop a typology of entrepreneurial transformation experienced by nascent entrepreneurs, thereby contributing to existing work on constructions of entrepreneurial identity. The main contribution of this paper is the conceptualization of four types of entrepreneurial transformation (minimal, career, personal, and existential) involving changes to the entrepreneur’s personal life, career, or both. The fourth quadrant of this typology—Existential Transformation, shows the highest level of transformation to both the personal and career lives of the entrepreneur. In this quadrant, we see emancipatory entrepreneuring as a fully agentic exercise, with one dually focusing on the identification and pursuit of change at the level of self to become the person one wants to be, integrated with the pursuit of a successful entrepreneurial venture that aligns what one does for a living with whom one wishes to be. We discuss all four types of entrepreneurial transformation, the factors that induce them, and implications to theory and practice.